A Study the Singing and Dramas in Yu Opera for Writing a Guidebook on Teaching 1st Year Students General Education in Shangqiu Normal University of Henan Province - Xiaoyu, Wang; Srisombut, Rujee (Journal of Roi Kaensarn Academi, 2024)
This study adopts mixed research methods, qualitative and quantitative research methods. In the research stage, interviews and observations were used. The researcher observed the learning status of first year students in Shangqiu Normal University. At the developmental stage, quantitative methods were used to draw conclusions through experimental design and statistical description. Thirty students in the first grade of Shangqiu Normal University were selected as experimental subjects for the Yu opera singing and drama teaching experiment. The effect of teaching Yu opera singing and drama was analyzed through pre-test and post-test. Using the basic theoretical knowledge of Yu opera, combining the author's study and expert interviews, and after exploring and researching the available academic materials, mainly focusing on the singing and drama of Yu opera for in-depth study and analysis, this paper develops a course plan for the first-year general education students. The Yu opera guidebook consists of four parts: "Basic Theoretical Knowledge of Yu Opera", "Yu Opera Singing", "Yu Opera Drama", and "Yu Opera Stage Performance". This course plan is finalized after expert interviews and aims to explore how to teach, sing and perform Yu opera well and to improve the development of students' Yu opera appreciation and aesthetic ability.